Factors Affecting Intradialytic Hypertension - Imam Hadi Yuwono; Anggorowati Anggorowati; Wahyu Hidayati (Indonesian Journal of Global Health Research, 2025)
Intradialytic hypertension, defined as an increase in blood pressure during or immediately after hemodialysis which results in postdialysis hypertension, has long been recognized to complicate the hemodialysis procedure, yet it is often largely ignored. Intradialytic hypertension affects the quality of life of patients undergoing hemodialysis and reduces their survival and increases mortality in CKD patients on hemodialysis. Objective to identify other factors that influence the occurrence of intradialytic hypertension. We conducted a literature search through the ScienceDirect, Scopus, and PubMed databases. The keywords used are "blood pressure" AND "hypertension" AND "dialysis" AND "intradialytic hypertension" AND "factor." The method used to compile information in this article is a scoping review, covering the period from 2020 to 2025, with article screening guided by the PRISMA flow. The article search selection results from ScienceDirect (n=45), PubMed Database (n=74), and Scopus Database (n=50) show that 9 articles can be selected according to the criteria. Articles were selected that correlate with the theme, specifically those discussing factors influencing intradialytic hypertension. Sodium dialysate, intradialytic weigh gian, diabetes mellitus, malnutrition, endothelial dysfunction, duration of hemodialysis, injection of erythropoietin hormone, blood phosphorus, and zinc level, are some factor all affect intradialytic hypertension.